2019
DOI: 10.1186/s12943-019-1111-2
|View full text |Cite|
|
Sign up to set email alerts
|

Circular RNA circFGFR1 promotes progression and anti-PD-1 resistance by sponging miR-381-3p in non-small cell lung cancer cells

Abstract: BackgroundImmune system evasion, distance tumor metastases, and increased cell proliferation are the main reasons for the progression of non-small cell lung cancer (NSCLC) and the death of NSCLC patients. Dysregulation of circular RNAs plays a critical role in the progression of NSCLC; therefore, further understanding the biological mechanisms of abnormally expressed circRNAs is critical to discovering novel, promising therapeutic targets for NSCLC treatment.MethodsThe expression of circular RNA fibroblast gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
194
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(198 citation statements)
references
References 48 publications
2
194
1
1
Order By: Relevance
“…In addition, some miRNAs are determinates of efficacy of immune checkpoint inhibitors. Zhang et al found that circFGFR1 acted as the miRNA sponge of miR-381-3p and induced the therapeutic resistance to PD-1 blockade [147]. Besides, Nakahara et al reported that the high levels of miR-16-5p, miR-17-5p, and miR-20a-5p were the indicators of responders of melanoma patients receiving anti-PD-1 therapy [148].…”
Section: The Effect Of Mirnas On Immunotherapymentioning
confidence: 99%
“…In addition, some miRNAs are determinates of efficacy of immune checkpoint inhibitors. Zhang et al found that circFGFR1 acted as the miRNA sponge of miR-381-3p and induced the therapeutic resistance to PD-1 blockade [147]. Besides, Nakahara et al reported that the high levels of miR-16-5p, miR-17-5p, and miR-20a-5p were the indicators of responders of melanoma patients receiving anti-PD-1 therapy [148].…”
Section: The Effect Of Mirnas On Immunotherapymentioning
confidence: 99%
“…Altogether, these findings suggest that targeting of specific tumor initiating/suppressive genes by varying non-coding RNAs could have an effect on these immune checkpoints by mimicking the role of immune checkpoint inhibitors. Alternatively, measuring patient response to anti-PD1 therapy in NSCLCs using circRNA and circulating miRNAs has been tested as novel approaches [131,132]. With the ability of circRNA to sponge various miRNA, inducing dysregulation could measure clinical response.…”
Section: Role Of Non-coding Rna In Evasion Of Host Immune Systemmentioning
confidence: 99%
“…Accumulating researches have revealed the signi cance roles of circRNA in lung cancer and COPD. For example, overexpressed circFGFR1 can promote the migration, invasion, and proliferation of NSCLC cells via sponging miR-381-3p [20]. Weimei Huang et.al performed circRNA microarray in NCI-H69 and NCI-H69AR cells and identi ed CircRNA cESRP1 as a potential prognostic biomarker in small cell lung cancer [21].…”
Section: Discussionmentioning
confidence: 99%